Absence of a structural transition up to 40 GPa in MgB2 and the relevance of magnesium nonstoichiometry - Bordet, P; Mezouar, M; Nunez-Regueiro, M; Monteverde, M; Nunez-Regueiro, MD; Rogado, N; Regan, K; Hayward, M; He, T; Loureiro, S; Cava, R (2001)
We report measurements on MgB2 up to ∼40 GPa. Increasing pressure yields a monotonous decrease of the lattice parameters and of the c/a ratio, but no structural transition down to parameters smaller than those of AlB2. The transition superconducting temperature also decreases with temperature in a sample-dependent way. The results are explained by an increase of the filling of the two-dimensional pxy bands with pressure, the Mg stoichiometry determining the starting position of the Fermi level. Our measurements indicate that these hole bands are the relevant ones for superconductivity.